Investment Dispute Settlement in the Building of CPEC and its Impact on the Neighboring Region - Hassan, Amna; Hassan Khalid, Ahmad (Pécs journal of international and European law, 2019)
The settlement of disputes amongst the investors and the nations in which they are set up is a key part of investment assurance under International Investment Agreements (IIAs). The majority of IIAs contain arrangements concerning investor-state dispute settlement (ISDS). Despite the fact that they had shaped some portion of IIAs for over 40 years, it was just in the most recent decade that the international investors started using these ISDS mechanisms as models of resolution and settlement of disputes under the IIAs. The ISDS movement amid the most recent decade has pro- duced a considerable number of cases touching upon key procedural and substantive parts of in- vestment law, in this way encouraging the improvement of a law that, is probably going to advance later on. The paper comprises of four main sections. Firstly, it analyzes the major developments as regards the available mechanisms for investment dispute resolution, from diplomatic protection to bilateral investment treaties and ISDS mechanism. Secondly, it refers to the ISDS mechanism as a most suitable arrangement for the resolution of investment disputes, discussing its suitability by comparing it to other available mechanisms. Thirdly, it focuses on the BITs and FTAs Model of Chi- na with Pakistan and other countries, in order to see the specific method mentioned therein to find provisions and procedures to be utilized for the ISDS mechanism. Fourthly, it considers the CPEC Agreement and its prospects for China and Pakistan, in addition to the building of a multilateral treaty context in the South-Asian Region similar to the type of integration of North-American coun- tries through the NAFTA Agreement.